2021
DOI: 10.3389/fpsyg.2021.738950
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Persuasive Effects of Testimonials on the Acceptance of Digital Stress Management Trainings Among University Students and Underlying Mechanisms: A Randomized Controlled Trial

Abstract: Objective: This experiment aims to investigate the influence of narrative information varying in the degree of perceived similarity and source credibility in supplemented testimonials on the acceptance of digital mental health services (digi-MHSs).Methods: In fall 2020, n=231 university students were randomly assigned to an active control group (aCG, n=55, “information only”) or one of three intervention groups (IGs) receiving information plus different testimonials being presented either by nonacademic staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“… 43 , 44 Promising strategies for promoting virtual mental health resource uptake could include, for example, the provision of simple, context-sensitive information about intervention applicability and credibility, such as through offering testimonials from previous service users and experts, as was shown to be effective in a recent study on digital mental health services with college students. 45 More generally, our study findings underscore the role of mental health literacy in shaping virtual resource access and utilization, and, in doing so, emphasize that fostering mental health literacy should be a key component of approaches to promote and protect population mental health. 42 , 46 …”
Section: Discussionsupporting
confidence: 58%
“… 43 , 44 Promising strategies for promoting virtual mental health resource uptake could include, for example, the provision of simple, context-sensitive information about intervention applicability and credibility, such as through offering testimonials from previous service users and experts, as was shown to be effective in a recent study on digital mental health services with college students. 45 More generally, our study findings underscore the role of mental health literacy in shaping virtual resource access and utilization, and, in doing so, emphasize that fostering mental health literacy should be a key component of approaches to promote and protect population mental health. 42 , 46 …”
Section: Discussionsupporting
confidence: 58%
“…Their perceived trustworthiness of the intervention and believability of its effectiveness relied on seeing tangible visualizations of their own progress in symptom reduction and hearing about the success of other users through statistics and testimonials. Aligned with this feedback, an evaluation of a digital stress management tool among university students found that adding positive testimonials increased the acceptance of the tool (Apolinário-Hagen et al 2021).…”
Section: Discussionmentioning
confidence: 79%
“…Some studies provided at best few insights into the design of AFIs on dMHSs. 54 , 55 , 64 67 For instance, Apolinário-Hagen et al 68 investigated the influence of information with or without varying testimonials but found no change in attitudes toward dMHSs among university students, while a follow-up experiment indicated positive findings on attitudes and acceptance using optimized AFI material with testimonials. 67 Research on future HCPs as a specific student group is even scarcer.…”
Section: Introductionmentioning
confidence: 99%
“… 54 , 55 , 64 67 For instance, Apolinário-Hagen et al 68 investigated the influence of information with or without varying testimonials but found no change in attitudes toward dMHSs among university students, while a follow-up experiment indicated positive findings on attitudes and acceptance using optimized AFI material with testimonials. 67 Research on future HCPs as a specific student group is even scarcer. However, this is an essential first step that has not been covered by research yet, which could be one reason for the low uptake rates of dMHSs.…”
Section: Introductionmentioning
confidence: 99%